Surface nano-hardness and microstructure of a single crystal nickel base superalloy after laser shock peening. (1st June 2017) - Lu, G.X.; Liu, J.D.; Qiao, H.C.; Zhou, Y.Z.; Jin, T.; Zhao, J.B.; Sun, X.F.; Hu, Z.Q.
Abstract: Nanoindention tests and SEM microstructure observations were conducted on a single crystal nickel base superalloy after laser shock peening (LSP). Distinct surface hardening behavior was found to occur under the selected LSP technology. A large discrepancy in γʹ areas happened on laser shocked regions and the large plastic deformation embodied in γʹ phases' deformation brought a significant hardening effect. Graphical abstract: Highlights: Nano-hardnesses of a single crystal superalloy suffered laser shock were measured. Microstructure evolution under laser shock for the single crystal superalloy was analyzed. Deformation mechanisms of γʹ precipitates and γ channels under laser shock were proposed.